A simple and cost-effective paper-based and colorimetric dual-mode detection of arsenic(iii) and lead(ii) based on glucose-functionalized gold nanoparticles. Issue 34 (10th June 2021) - Sahu, Bhuneshwari; Kurrey, Ramsingh; Deb, Manas Kanti; Shrivas, Kamlesh; Karbhal, Indrapal; Khalkho, Beeta Rani
Abstract : We report a simple and cost-effective paper-based and colorimetric dual-mode detection of As(iii ) and Pb(ii ) based on glucose-functionalized gold nanoparticles under optimized conditions. Abstract : We report a simple and cost-effective paper-based and colorimetric dual-mode detection of As(iii ) and Pb(ii ) based on glucose-functionalized gold nanoparticles under optimized conditions. The paper-based detection of As(iii ) and Pb(ii ) is based on the change in the signal intensity of AuNPs/Glu fabricated on a paper substrate after the deposition of the analyte using a smartphone, followed by processing with the ImageJ software. The colorimetric method is based on the change in the color and the red shift of the localized surface plasmon resonance (LSPR) absorption band of AuNPs/Glu in the region of 200–800 nm. The red shift (Δ λ ) of the LSPR band observed was from 525 nm to 660 nm for As(iii ) and from 525 nm to 670 nm for Pb(ii ). The mechanism of dual-mode detection is due to the non-covalent interactions of As(iii ) and Pb(ii ) ions with glucose molecule present on the surface AuNPs, resulting in the aggregation of novel metal nanoparticles. The calibration curve gave a good linearity range of 20–500 μg L −1 and 20–1000 μg L −1 for the determination of As(iii ) and Pb(ii ) with the limit of detection of 5.6 μg L −1 and 7.7 μg L −1 for both metal ions, respectively. The possible effects of different metal ions and anions were also investigated but did not cause any significant interference. The employment of AuNPs/Glu is successfully demonstrated for the determination of As(iii ) and Pb(ii ) using paper-based and colorimetric sensors in environmental water samples.